1993
DOI: 10.2214/ajr.161.3.8352118
|View full text |Cite
|
Sign up to set email alerts
|

Free vascularized fibular grafts: radiographic evidence of remodeling and hypertrophy.

Abstract: OBJECTIVE.A study was undertaken to determine the growth potential and radio- occurs to a much greater extent in some grafts than in others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
7

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 1 publication
0
20
0
7
Order By: Relevance
“…Various articles have reported hypertrophy incidence ranging from 38 – 90% 2024. Reduced hypertrophy was seen when the graft was by-passed with internal fixation,23 but some authors found no difference in the hypertrophy with regard to the method of fixation 2021. When cancellous grafts were placed along the fibular graft no hypertrophy was seen after the cancellous graft ossified, due to stress shielding 24.…”
Section: Discussionmentioning
confidence: 99%
“…Various articles have reported hypertrophy incidence ranging from 38 – 90% 2024. Reduced hypertrophy was seen when the graft was by-passed with internal fixation,23 but some authors found no difference in the hypertrophy with regard to the method of fixation 2021. When cancellous grafts were placed along the fibular graft no hypertrophy was seen after the cancellous graft ossified, due to stress shielding 24.…”
Section: Discussionmentioning
confidence: 99%
“…Although hypertrophy often occurs and can be seen on radiographs at an average of 18 months after surgery, hypertrophic bone fractures have been reported (Lazar et al 1993). A vascularized fibula graft in the leg should be protected against fatigue fracture during the first few years after implantation.…”
Section: Discussionmentioning
confidence: 99%
“…17,[37][38][39][40] Hypertrophy is more common when the limb is mechanically loaded. De Boer et al found hypertrophy in 43 % of the mechanically loaded lower extremities and in only 20 % of the upper extremities.…”
Section: Discussionmentioning
confidence: 99%